Lives and Livelihoods in Smallholder Farming Systems of Senegal: Impacts, Adaptation, and Resilience to COVID-19 - Prakash Kumar Jha; Gerad Middendorf; Aliou Faye; B. Jan Middendorf; P. V. Vara Prasad (Land, 2023)
The COVID-19 pandemic has had immediate and cascading impacts on global agricultural systems. In Senegal, the immediate impacts include inaccessibility of inputs due to disruption in markets and supply chains, availability of labor, and changes in crop and livestock management practices. To understand the range of impacts on the biophysical and socioeconomic dimensions of smallholder farming systems, a survey was designed to identify the risk factors, assess the impacts, and explore appropriate mitigation strategies. The survey was administered to 917 smallholder farmers in 14 regions of Senegal in collaboration with a national farmer’s organization and the Senegalese Institute of Agricultural Research (ISRA). The sample was comprised of farmers (men and women) and was stratified in each region to ensure representation from all agroecological zones of the country. The survey examined variables such as access to inputs, ability to plant, impacts on yields, markets, labor, the gendered division of labor, food security, and community well-being. The survey response indicated that 77.7% of respondents experienced a reduction in access to inputs, 70.3% experienced a reduction in ability to plant crops during the planting season, 57.1% experienced a reduction in ability to rent farm machinery, and 69.2% reported a reduction in yields. Similar findings were observed for labor, market conditions, and adaptation measures to reduce the impacts on farming systems and household livelihoods. This study advances the research on characterizing risk factors, assessing the impacts, and designing mitigation strategies for strengthening smallholder farming systems resilience to future shocks.